GEN Z AND THE FUTURE OF BANKING: AN ANALYSIS OF DIGITAL BANKING ADOPTION - Chitra Laksmi Rithmaya; Herwin Ardianto; Evi Sistiyarini (Jurnal Manajemen dan Kewirausahaan, 2024)
In the era of digitalization, a digital bank was the development of banking services. Bank innovation led to innovation in providing various alternative services and improved the ease of transactions for digital banking applications. This study aimed to discuss how digital banks used service features using a modified UTAUT2 approach. The data used was that of respondents belonging to generation Z in Indonesia who used digital banking services on mobile devices. Data analysis was done using PLS-SEM. The findings demonstrated that performance expectancy was the highest variable determining behavioral intention and used behavior. Habit and trust on service provider also predicted intention, and facilitating conditions also had a direct effect on usage behavior when adopting digital banking in generation Z. Surprisingly, effort expectancy, social influence, hedonic motivation, price value, and trust in the internet did not have a significant relationship, for which some possible reasons were explained further. In this article, theoretical and practical implications were also discussed.